A quasi-experimental evaluation of partnerships for success's impact on community-level ethanol and prescription drug poisoning rates. (August 2019) - Morgan-Lopez, Antonio A.; Elek, Elvira; Graham, Phillip W.; Saavedra, Lissette M.; Bradshaw, Michael; Clarke, Tom
Abstract: The emerging dual threats of underaged drinking (UAD) and prescription drug misuse (PDM) require sustained prevention efforts across multiple levels of interventions. In response to the continuing proliferation of UAD and PDM among youth and young adults, the Substance Abuse and Mental Health Services Administration (SAMHSA) developed the Partnerships for Success (PFS) program. Across five cohorts funded from 2012 to 2016, PFS created linkages between health care providers, treatment and prevention services providers, government agencies, and nonprofit organizations for the delivery of multiple sets of services (e.g., prevention education, community activities, screening) targeted toward UAD and PDM. This paper reports on the impact of the PFS program on reductions in ethanol and prescription drug poisoning exposures as reported from data in the National Poisoning Data System (NPDS). Across 35 States, communities targeted by PFS interventions were compared to non-targeted communities using a non-equivalent comparison groups design and propensity score weighting. Using propensity-weighted, multilevel latent growth modeling, steeper reductions in ethanol and prescription drug poisoning exposure call rates were observed in States which had a higher proportion of communities participating in PFS. Grantee-level longitudinal analogs to Cohen's d effect sizes ranged from −0.24 to −0.97, whereas PFS' effects on individual communities (net of Statewide effects) were negligible. The study serves as a unique exemplar of using the NPDS to extract community-level intervention effects that might otherwise be "hidden" within epidemiological data while underscoring the cumulative effects of PFS' community-level efforts in stemming the tide on underaged drinking and prescription drug misuse. Highlights: The emerging threats of underaged drinking (UAD) and prescription drug misuse (PDM) require sustained prevention efforts SAMHSA funded 70 grantees under Partnerships for Success (PFS) to mobilize local organizations in their efforts to reduce UAD and PDM We examined differences over time between PFS communities and comparison communities in UAD and PDM poisoning exposures Higher proportions of PFS communities within States were related to reductions in ethanol and prescription drug poisonings